Recuperación de oro por gravimetría de mineral proveniente del Distrito Minero Nambija Condominio Sur - Cabrera Carrión, Santiago Israel (2014)
The aim of the present research is to apply the gravimetric methods for the gold concentration, to be more specific in concentration table and knelson centrifugal concentration from material of Nambija “south condominiun”. The mineralogy was determined using the polarized light microscopic analysis which was obtained: 41% pyrrhotite, 22% Sphalerite, 13% Pyrite, 3% Chalcopyrite and Ganga with 12%. For the realization of the test whit concentration table, we consider the grain size, obtaining the better results using a number 125 mesh aim with a performance of 37,78%. For the knelson centrifugal concentration test, we apply; size of grain and pressure, also performed a second feed, it using the first process tailingsthus proceeded to recalculation of grain size with wich the highest values using a number 180 mesh, and using too a 1PSI pressure, we obtain a better performance of 61,47%. The development procees combination was in secuence that us used first in the concentration table, then the concéntrate grinding took to set the size of appropiate grain and finally using the knelson centrifugal concentration, we obtain a better performance of 87,95%.